HUBUNGAN KELENGKAPAN BAHAN BACAAN DI TAMAN BACAAN MASYARAKAT DAYUNG ILMU TERHADAP MINAT BACA ANAK SD DI DESA PERLIS KAB. LANGKAT - Rosdiana Rosdiana; Ayu Rizky Amalia (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This study aims to see the completeness of reading material in TBM Dayung Ilmu, reading interest of elementary school age children, and whether there is a relationship between reading material completeness in TBM Dayung Ilmu with reading interest of elementary school aged children in Perlis Village, Langkat Regency. The research method used is quantitative research. The sample in this study may be 50 people. The results showed that the relationship between the completeness of reading materials and the interest obtained by the calculation of the regression equation was Y = 30.6 + 0.402 X. Meanwhile, the meaning of X and Y was rcount> rtable, namely 0.489> 0.279, and hypothesis testing was tcount> ttable, namely 3.885. > 1,677, then this research hypothesis is accepted.Keywords: Reading Materials, Reading Interests